Overexposed and Understudied: Environmental Risks Among Older Adults Experiencing Homelessness in Phoenix, Arizona - Zachary Van Tol; Ariane Middel; Jennifer K. Vanos; Kristin M. Ferguson (GeoHealth)
Abstract Individuals experiencing homelessness are highly vulnerable to urban environmental hazards, such as heat and air pollution, due to a lack of stable housing and limited access to indoor or cooled spaces. These risks are heightened for older adults and individuals with preexisting health conditions. With intensifying summer heat in the American Southwest and the persistence of urban homelessness, this study explores how older adults experiencing homelessness in Phoenix, Arizona perceive and interact with heat and air pollution as well as the adequacy of available coping resources and information. A survey was co‐produced with community members with lived experience. A sub‐group of community members assisted in proctoring the surveys among adults 55 and older at a downtown service agency. Survey results informed the location of data collection using MaRTy—a mobile biometeorological cart—and remotely sensed fine particulate matter (PM2.5). Findings reveal that heat and air pollution significantly influence travel decisions and contribute to health issues for many respondents. Midday and evening thermal radiation levels regularly exceeded safe thresholds, while PM2.5 concentrations often surpassed annual air quality guidelines, though they posed less acute health risks. Most participants reported awareness of health risks and employed strategies to reduce exposure. However, many expressed that city‐level, public resources are insufficient to prevent heat‐ and air pollution‐related health issues. Findings underscore the need for targeted interventions—such as better access to transportation and essential healthcare and extended hours of operation for service providers—to enhance resource accessibility and mitigate environmental health risks for vulnerable populations.